(3E, 8E)-3, 8-Bis(2-oxoindolin-3-ylidene)naphtho-[1, 2-b:5, 6-b′]difuran-2, 7(3H, 8H)-dione (INDF) based polymers for organic thin-film transistors with highly balanced ambipolar charge transport characteristics. Issue 70 (27th July 2015) - Deng, Yunfeng; Sun, Bin; He, Yinghui; Quinn, Jesse; Guo, Chang; Li, Yuning
Abstract : INDF polymers exhibit highly balanced ambipolar characteristics with hole and electron mobilities up to 0.51 cm 2 V −1 s −1 and 0.50 cm 2 V −1 s −1, respectively. Abstract : Two donor–acceptor (D–A) conjugated polymers, PINDFTT and PINDFBT, based on a novel electron acceptor, (3 E, 8 E )-3, 8-bis(2-oxoindolin-3-ylidene)naphtho-[1, 2- b :5, 6- b ′]difuran-2, 7(3 H, 8 H )-dione (INDF), are synthesized for solution processed organic thin-film transistors. Both polymers exhibited highly balanced ambipolar characteristics with hole and electron mobilities up to 0.51 cm 2 V −1 s −1 and 0.50 cm 2 V −1 s −1, respectively.